Sequence-based epitope mapping of high pathogenicity avian influenza H5 clade 2.3.4.4b in Latin America - Ospina-Jimenez, Andres F.; Gomez, Arlen P.; Osorio-Zambrano, William F.; Alvarez-Munoz, Santiago; Ramirez-Nieto, Gloria C. (Frontiers in Veterinary Science, 2024)
High Pathogenicity Avian Influenza (HPAI) poses a significant threat to public and animal health. Clade 2.3.4.4b recently emerged from the Eastern hemisphere and disseminated globally, reaching the Latin American (LATAM) region in late 2022 for the first time. HPAI in LATAM has resulted in massive mortalities and culling of poultry and wild birds, causing infection in mammals and humans. Despite its meaningful impact in the region, only occasional evidence about the genetic and epitope characteristics of the introduced HPAI is reported. Hence, this study seeks to phylogenetically characterize the molecular features and the source of HPAI in LATAM by evaluating potential antigenic variations. For such a purpose, we analyzed 302 whole genome sequences. All Latin American viruses are descendants of the 2.3.4.4b clade of the European H5N1 subtype. According to genomic constellations deriving from European and American reassortments, the identification of three major subtypes and five sub-genotypes was achievable. Based on the variation of antigenic motifs at the HA protein in LATAM, we detected three potential antigenic variants, indicating the HA-C group as the dominant variant. This study decidedly contributes to unraveling the origin of the 2.3.4.4b clade in LATAM, its geographic dissemination, and evolutionary dynamics within Latin American countries. These findings offer useful information for public health interventions and surveillance initiatives planned to prevent and manage the transmission of avian influenza viruses.